(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study seeks, in its analysis of the reading of the explicit source, to reveal the significance of the readings in it and to give preference to the most obvious reading. According to the context of the place, and the organized relations to the textual discourse of the similar verses in which it was mentioned, In this research is an idea that strives to anticipate the similarity of its word in the pronunciation of the explicit source, a difference in readings resulted in a new semantics. It is known that there are multiple readings; For the multiplicity of its readers and for every reading that differs from the other, and this is what the study discusses and analyses it with the use of the books of linguistic dictionaries, readings, interpretations, the sciences of the Quran and other books in order to achieve the goal of the study.